Training in Writing Scientific Works and Popular Science Books for Teachers at SMKN 34, Central Jakarta - Redjeki Agoestyowati; Umi Hani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Some vocational teachers still need help writing scientific papers and publications or writing textbooks and general books, which can be used as one of the requirements for promotion or position. This writing training aims to share knowledge with teachers at SMKN 34 Jakarta about techniques for writing scientific papers, textbooks, and general books, as well as the systematics of writing and how to publish scientific papers. The method is through the sharing method by giving lectures to the participants, discussions, presentations, and questions and answers. Outside of the training session, writing assistance is also given to several teachers who are ready with their articles so they can publish a work or publish it in journal form. The result of this training is that the participants are very enthusiastic about participating in the training. It can be seen from the attendance of participants as much as 100% from the opening to the final session. After the training, the participants can understand how to write and publish scientific articles in accredited national journals. Participants also understand how to make a reference book or general book so that national publishers can publish it. This training was supposed to be successful because their understanding of the world of writing increased, the participant's response to this activity was very positive, and several teachers had prepared articles from previous research to be published in one of the accredited national journals,